Manajemen Pembelajaran Nahwu Shorof di Pondok Pesantren Apik Kesugihan - Ulfatul Khasanah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
APIK Islamic boarding schools in learning management must refer to general managerial patterns that begin with planning and end with evaluation, while salafiyyah Islamic boarding schools which are mono managerial in all respects include their nahwu shorof learning which makes learning books in Islamic boarding schools only take place naturally. Nahwu shorof learning management applied in PP. APIK which in fact is a boarding school that still maintains the salafiyyah tradition and has not systematically implemented the nahwu shorof learning management pattern in detail. The purpose of this study was to determine the natural background of PP. APIK, planning, organizing, implementing and evaluating nahwu shorof learning. The theory used in this study is learning management according to H.E. Mulyasa in a paper entitled MPDI curriculum development according to KKNI and SNPT 27/11/2015 states that micro-management of learning includes planning, implementation and evaluation. The method used in this research is qualitative with a case study approach. Data collection techniques include observation, interviews and documentation studies. The results of this study concluded that the learning management of Nahwu Shorof at APIK Islamic boarding schools can be described from planning, implementation and evaluation. Learning planning at the APIK Islamic boarding school is based on the ability of the students themselves, if the students are still unfamiliar with their Islamic boarding school's knowledge in learning books, then it is adjusted to be oriented towards studying books that are basic to the highest. The implementation of nahwu shorof learning at the APIK Islamic boarding school is divided into two classical systems, namely ibtida/tsanawi. The evaluation of nahwu shorof learning at the APIK Islamic boarding school is oriented towards the completeness of the material, one book is studied continuously and repeatedly until in the end the students understand the contents of the book they are studying with the sorogan, bandungan and rote systems.